Reconstruire à l'école, autant que possible, l'authenticité d'un passé rendu intelligible - Charles Heimberg (Université de Provence, 2016)
School transmission of an intelligibility of the past is subject to all kinds of pressure in the public space, and even a real tyrannical orthodoxy. Countless actors proclaim a sententious tone that should be school history, usually in a straitjacket of identity and prescriptive far from any scientific requirement. But this is for the school context, the didactic transposition of a social science discipline whose purpose is to promote a self-critical thought and discernment to act in the social world. This objective requires giving up both to a fall on a closed and inculcation of cumulative knowledge and education is sententious, is so entertaining it would not allow students to work this feeling of strangeness that should mark any relationship past and its differences. It is however possible to make them tasty build knowledge that enable them to better understand the world in which they live.